Global competitiveness and industrial growth in Taiwan and the Philippines - Kuo, Cheng-tian, 1957- (Pitt series in policy and institutional studies., 1995)
Why have Taiwan and the Philippines evolved so differently in industrial growth? After careful examination, Cheng-Tian Kuo concludes that corporatist links between industry and government are key factors explaining rapid economic progress in East Asia. The impact of business associations on industrial growth has long deserved closer analysis. Using important new research data - business association proceedings, newly published government documents, and newspaper reports - Kuo presents a refreshing reassessment of the role of private-sector alliances on state policy and national economic vitality in the Far East.